Pseudomonas fluorescens Alters the Intestinal Barrier Function by Modulating IL-1β Expression Through Hematopoietic NOD2 Signaling. Issue 3 (5th February 2015) - Alnabhani, Ziad; Montcuquet, Nicolas; Biaggini, Kelly; Dussaillant, Monique; Roy, Maryline; Ogier-Denis, Eric; Madi, Amar; Jallane, Abdelhak; Feuilloley, Marc; Hugot, Jean-Pierre; Connil, Nathalie; Barreau, Fréderick
Abstract : Background: Ileal Crohn's disease is related to NOD2 mutations and to a gut barrier dysfunction. Pseudomonas fluorescens has also been associated with ileal Crohn's disease. The aim of this study was to determine the impact of P. fluorescens on the paracellular permeability in ileum and Peyer's patches. Methods: To explore this question, in vivo and ex vivo experiments were performed in wild-type, Nod2 −/−, Nod2 2939iC, and IL - 1R −/− mice together with in vitro analyses using the Caco-2 (epithelial) and the THP-1 (monocyte) human cell lines. Results: Pseudomonas fluorescens increased the paracellular permeability of the intestinal mucosa through the secretion of IL-1β by the immune cell populations and the activation of myosin light chain kinase in the epithelial cells. Induction of the IL-1β pathway required the expression of Nod2 in the hematopoietic compartment, and muramyl dipeptide (a Nod2 ligand) had an inhibitory effect. Conclusions: Pseudomonas fluorescens thus alters the homeostasis of the epithelial barrier function by a mechanism similar to that previously observed for Yersinia pseudotuberculosis . This work further documents a putative role of psychrotrophic bacteria in Crohn's disease.